Pristine No More: Microplastics and Per- and Polyfluoroalkyl Substances (PFAS) Reveal Two Distinct Contamination Pathways in the Confined Volcanic Aquifers of Savusavu, Fiji - Daphne Marshall; Shanti Narayan; Jone Tavola (Program Pascasarjana Universitas Sriwijaya, 2026)
Background: Remote oceanic-island aquifers are historically classified as pristine freshwater reserves, largely immune to global anthropogenic contamination; the ubiquity of emerging contaminants challenges this assumption. Objective: To present the first joint baseline of microplastics (MPs) and per- and polyfluoroalkyl substances (PFAS) in the confined volcanic (basaltic) aquifer of the Savusavu region, Vanua Levu, Fiji. Methods: Groundwater was sampled from 15 boreholes (45–120 m depth) during the dry season under strict fluoropolymer-free and contamination-controlled protocols. PFAS were quantified by solid-phase extraction with liquid chromatography–tandem mass spectrometry (SPE-LC-MS/MS) and MPs by wet-peroxide oxidation, stereomicroscopy and micro-Raman spectroscopy; data were analysed by one-way ANOVA with Tukey HSD and eta-squared, Pearson correlation, principal component analysis (PCA) and contamination/hazard indices. Results: MPs occurred in 87% of wells (mean 4.08 ± 2.56 MPs/L, fibre-dominated) and PFAS in 100% (PFOA 6.35 ± 4.35 ng/L; PFOS 4.10 ± 2.95 ng/L). Concentrations declined significantly with depth, most steeply for MPs (r = −0.93, p < 0.001). PFOA exceeded the 4.0 ng/L US EPA maximum contaminant level in 10 of 15 wells, whereas nitrate and chloride remained within WHO limits. PCA explained 86% of variance and resolved two transport pathways: a dissolved axis (PFOA–PFOS–nitrate) and a particulate fracture-flow axis (MP–turbidity–chloride). Conclusion: Confined volcanic aquifers in remote Pacific islands are therefore not entirely pristine but act as sinks for global trace contaminants, necessitating the integration of emerging contaminants into Pacific island groundwater policy.